How activist investors value target firms: Evidence from hedge fund presentations - Maximilian Pfirrmann; Korbinian Eichner (Journal of Corporate Accounting & Finance, 2024)
This research study provides insights on how activist hedge funds perform valuation analyses of target firms. Relevant data was hand-collected from a sample of activist hedge fund presentations. Based on the hedge funds' valuation analyses, the undervaluation of the target firms amounts to approximately 30%, compared to the targets' current share price. Besides, activist investors derive a value enhancement potential from their proposed strategies of approximately 70% to the targets' current share price. These valuation results rely predominately on trading multiples. The dominant multiples are Enterprise value/EBITDA (EV/EBITDA) and Price/Earnings (P/E). Further, applied multiples are mainly forward-looking, and the predicted performance measures are primarily consensus estimates. Besides, hedge funds sometimes adjust multiples arbitrarily to increase the comparability. Our results confirm that short-term investors rely predominately on pricing analyses in their valuations.
Keywords: 650; corporate finance; corporate valuation; hedge funds; shareholder activism